PERBEDAAN EFEKTIFITAS PERANGKAP T1KUS T1PE LEHER lERAT DAN CAGE TRAP DALAM MENANGKAP T1KUS - Sefrina Betty Kirana; Irwan Sulistio; Suroso Bambang Eko Warno (GEMA LINGKUNGAN KESEHATAN, 2013)
Rats may also be as vectors and cause disease in humans and pets. Rats can be controled bychemical, physical! mechanical, biological, biophysical and cultural. This study aimed tocompare the effectiveness of neck snares trap and cage trap on chatching rats. Research typewas quasi-experiment. The object of the research was rats trap. Variables of it was types oftraps that caught rats and mice. There was no difference in effectiveness between neck snaresand cage trap. Cage trap type can be used at home as rat control. It is very available in themarket and more economical than neck snare trap.Key Words : Rats, Rat Traps, Neck Snare, Cage Trap